Laser modeling : a numerical approach with algebra and calculus - Csele, Mark. (Boca Raton : CRC Press/Taylor & Francis, 2014)
'Preface The approach taken in this book is simple present laser theory in an understandable way and one that can be applied immediately, and numerically, to real laser systems. With that in mind, the approach in this text is to present each theory along with a real, solved example--in most cases, based on commercial lasers. As a professor of laser science, I am fortunate to have a lab equipped with many different types of lasers; many of those lasers are included here in examples. In making the theory'accessible,' both a calculus-based and an algebraic approach are shown in tandem; a prime example of this is the presentation of both the calculus-based Rigrod model and an algebra-based model for the prediction of various laser parameters in Chapters 3 and 4. Readers drawn to numerically grounded solutions to problems (dare we say'engineers'?) will find the algebraic approach a refreshing demonstration of how concepts actually work and are applied, while those with more mathematical thought processes will appreciate the complementary calculus-based models. Either way, the results are similar (and, as I tell my students, it doesn't matter how you learn it). As an educator, I appreciate the fact that we all learn in different ways. The actual use of algebra-based solutions originated with our four-year bachelor program at Niagara College. Although at the inception of the program we intended to use calculus-based theory exclusively, it became apparent that students were spending more time on the math than on the concepts (i.e., they were often'buried in the math,' with the mathematical rigor of solutions getting in the way of understanding the concepts)'--
Includes bibliographical references and index.
Keywords: Lasers -- Mathematical models; Laser beams -- Mathematical models; Numerical analysis